HAMBATAN PROSES AKSELERASI PENERBITAN SERTIFIKAT RECHTS CADASTER:PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP DI KABUPATEN BANDUNG - Ummah, Alda jamilathul; Nurliawati, Nita; Sodik Sudrajat, Achmad; Alikha Novira (CREATIVE RESEARCH JOURNAL, 2024)
Land registration is seen as a way to provide legal certainty for the control and ownership of land parcels in accordance with Article 19 Paragraph (1) of the Basic Agrarian Law. In order to reduce the problems in the land sector, the government issued a program to facilitate the community in managing land title certificates. This study used a qualitative descriptive approach. The data obtained were analyzed using the theory of policy implementation model from Grindle (1980). The data sources come from primary data obtained through interviews, observations, and documentation studies as well as secondary data in the form of regulations related to the implementation of the complete systematic land registration program (PTSL). Data analysis techniques using fishbone diagrams. The results showed that the implementation of a complete systematic land registration program in Bandung Regency has been carried out in accordance with the stages of program implementation. However, in the implementation, there are still several inhibiting factors in human resources, public awareness, and completeness of application files. Recommendations to accelerate the issuance of land certificates by improving the competence of human resources and compiling internal technical guidelines (PTSL pocketbook).